Accuracy of the Milan System for Detecting Neoplastic vs Non-Neoplastic Salivary Gland Lesions: A Retrospective Review. (28th October 2021) - Fakhri, N; Khokhar, H; Khreefa, Z; Shahmirzadi, M; Bhalla, R
Abstract: Introduction/Objective: Overlapping morphology and heterogeneity of salivary gland tumors (SGT) poses a diagnostic challenge. FNA is commonly used diagnostic tool for evaluation of superficial and deep lesions of any site, but above limitations restrict its maximum utility. To standardize reporting and to address above limitations, Milan system (MS) of reporting salivary gland cytology, has been developed and implemented by labs. We conducted a retrospective study, applying MS to salivary gland lesions (SGL) to evaluate its accuracy and usefulness in discriminating between neoplastic and non-neoplastic conditions, and thus directing patient management (PM) Methods/Case Report: 10 yr retrospective review was performed to include patients with FNA for SGL, cytology diagnosis categorized using MS, cytology-histology (CH) correlation performed, and patients' charts reviewed for follow up. Attention given to diagnostic discrepancies between MS categories and the histologic diagnosis Results (if a Case Study enter NA): 152 patients (20-88yrs) were retrieved, peak incidence 40-49 yrs; M:F ratio 1.2:1. Distribution of the cases in the MS categories: Non-diagnostic (ND) 24, Non-neoplastic (NN) 33, Atypia of Undetermined Significance (AUS) 4, Neoplasm (N) 71, Suspicious for malignancy (SUN) 7, and Malignant (M) 10. 60 cases identified with follow-up histology, of which 51 cases were correlated, distributed as 4 ND, 4 NN, 0 AUS, 37 N, 3 SUN, and 3 M. The uncorrelated 9 cases were distributed as 4 ND due to scant sampling; 2 NN, histologically Warthin's tumor and sialolipoma; 2 AUS, histologically basal cell neoplasm and infarcted Warthin's tumor; 1 malignant, histologically cystic mucoepidermoid carcinoma; 0 cases for neoplastic and suspicious for malignancy categories Conclusion: Milan System is a useful cytologic tool for diagnosing and segregating patients with salivary gland pathologies, however, our study shows MS to be more reliable diagnostic tool with higher accuracy (combined 98%) in N, SUN & M categories as compared to ND, NN & AUS categories (combined 50%)